2006
DOI: 10.1249/01.mss.0000228953.52473.ce
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Extent of Neural Activation during Maximal Effort

Abstract: We conclude that CAR overestimates the extent of neural activation during an MVIC because the 3D shape of the thigh is altered. This will change electric current flow to the axonal motor neuron branches and limit the artificially evoked torque, thereby resulting in an overestimation of CAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Following a 3-min stimulation protocol, the proportion of muscle activated as computed using MRI images was substantially less than that computed using MVC-superimposed electrical stimulation methods (Kendall et al 2006). Although Adams et al (1993) also found considerably less than 100% of muscle Wbers activated using T 2 -weighted images following electrical stimulation, they noted "…moving both electrodes… markedly changed the pattern of stimulation of m. quadriceps femoris."…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Following a 3-min stimulation protocol, the proportion of muscle activated as computed using MRI images was substantially less than that computed using MVC-superimposed electrical stimulation methods (Kendall et al 2006). Although Adams et al (1993) also found considerably less than 100% of muscle Wbers activated using T 2 -weighted images following electrical stimulation, they noted "…moving both electrodes… markedly changed the pattern of stimulation of m. quadriceps femoris."…”
Section: Discussionmentioning
confidence: 92%
“…Although Adams et al (1993) also found considerably less than 100% of muscle Wbers activated using T 2 -weighted images following electrical stimulation, they noted "…moving both electrodes… markedly changed the pattern of stimulation of m. quadriceps femoris." Thus, although the MRI data suggests that maximal eVort results in the activation of only 75% of muscle Wbers (Kendall et al 2006), this might be partly attributable to the diYculty of fully activating motoneurons using electrical stimulation. Moreover, Kendall et al (2006) used an electrical stimulation protocol that elicited only 49% MVC.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As well as differences in muscle fibre-type composition between different muscle groups (Johnson et al 1973), variations in electrical muscle stimulation protocols (more specifically the pulse duration or frequency of stimuli) used to generate a joint moment may partly explain the variability in specific tension values reported between some studies (Maganaris et al 2001;Gorgey et al 2006). In addition, voluntary muscle activation was determined using the ITT in the present study, while a combination of T2-MRI and neuromuscular stimulation has been used for the same purpose in several other investigations (Adams et al 1993;Kendall et al 2006). The latter method generally demonstrates a lower voluntary muscle activation capacity (*75%) than the ITT (*90%) and hence would lead to differences between studies when calculating muscle specific tension in vivo.…”
Section: Discussionmentioning
confidence: 98%